Synthesis and Characterization of Nanoporous Carbon from Sugarcanne Bagasse (Saccharum officianarum) with ZnCl2 Activator by Ultrasonic Irradiation as Electrochemical Energy Storage Material - Arniati Labannia; Nasir La Hasan; Maming Maming; muhammad zakir (Hasanuddin University, 2015)
A study on synthesis and characterization of nanoporous carbon derived from sugarcane bagasse (Saccharum officianarum) by ultrasonik irradiation using ZnCl2 activator for electrochemical capasitor application has been investigated. Nanoporous carbon is a basic material for the electrode in the electrochemical energy storage. Nanoporous carbon has been synthesized based on three-steps procedures, i.e. carbonization in temperature of 350 0C, silica extraction, and activation using ZnCl2 with ultrasonic irradiation. Activated carbon with irradiation showed an increasing in intensity of the –OH functional group stretch at wave number of 3419,79. The results of XRF analysis showed the highest content of oxide compound in the activated carbon was ZnO as 97,06%, and result of XRD analysis showed that activated carbon has both amorphous and crystalline. The result of SEM analysis showed that the pores evolvement of irradiated activated carbon was better than un-irradiated activated carbon, with diameter of the pores 1,5 to 2 µm. The surface area of the carbon in optimum temperature of 30 oC for 60 minutes was 171, 2802 m2/g and the energy storage capacity was 0,3284 x 10-5 F/g.